Fire protection systems - Jones, A. Maurice (Jones & Bartlett Learning, 2021)
The third edition of Fire Protection Systems meets and exceeds the National Fire Academy's Fire and Emergency Services Higher Education (FESHE) course objectives and outcomes for the Associate's (Core) course Fire Protection Systems (C0288). The Third Edition provides a comprehensive and concise overview of the design and operation of various types of fire protection systems, including fire alarm and detection systems, automatic fire sprinkler systems, special hazard fire protection systems, smoke control and management systems, and security and emergency response systems. The Third Edition includes: An emphasis on testing and inspection-Testing and inspection are stressed throughout and are reinforced through discussions of design and installation standards, testing and inspection processes and requirements, and common system impairments. Updated model code overview-An overview of the model code development process is presented to assist students in understanding the origin and ongoing significance of building, fire, and life safety issues and requirements. Case Studies-Each chapter begins with a case study that highlights actual events and lessons learned to emphasize the importance of designing, installing, inspecting, and maintaining fire protection systems to effectively fight fires. Additional case studies close each chapter and provide students a means to test their knowledge of the chapter concepts in the context of a fictional case.